EVALUATION of COMBINATION ABILITY of SPRING BARLEY VARIETIES ACCORDING TO QUANTITATIVE CHARACTERISTICS IN THE CONDITIONS of NORTH STEPPE of UKRAINE - Ващенко, В. В.; Шевченко, О. О. (Scientific Progress & Innovations, 2014)
A total of diallel analysis varieties of spring barley Donetskiy 12, Donetskiy 14, Donetskiy 15, Prairie, Galactic set features genetic control variability characteristics: plant height, number of grains per ear, 1000 grain weight in accordance with the ratio of variance of specific combining ability (SSI) and general combining ability (ZKZ). Identified and proposed as a source of variety traits plant height and Donetsk 14, Galactic, the number of grains per ear sort Prairie, weight of 1000 grains Donetskiy 15. Samples of high and stable levels of combining ability is proposed to use in breeding work have beeen celected.